2023
DOI: 10.1002/art.42489
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Neutrophil Extracellular Trap Antibodies in Antiphospholipid Antibody–Positive Patients: Results From the Antiphospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Networking Clinical Database and Repository

Abstract: Objective This study aimed to elucidate the presence, antigen specificities, and potential clinical associations of anti–neutrophil extracellular trap (anti‐NET) antibodies in a multinational cohort of antiphospholipid (aPL) antibody–positive patients who did not have lupus. Methods Anti‐NET IgG/IgM levels were measured in serum samples from 389 aPL‐positive patients; 308 patients met the classification criteria for antiphospholipid syndrome. Multivariate logistic regression with best variable model selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…In another study, IgG and IgM antibodies to NETs measured by ELISA were significantly elevated in patients with primary APS and in SLE without aPL relative to the healthy controls [58]. In a recent larger cohort of primary APS, 45% of the aPL-positive patients had IgG and/or IgM anti-NET antibodies [59]. Importantly, an analysis of the associations of anti-NET antibodies with clinical manifestations revealed that IgG antibodies were associated with lesions affecting the white matter of the brain, while IgM antibodies were tracked with complement consumption.…”
Section: Anti-net Antibodiesmentioning
confidence: 89%
“…In another study, IgG and IgM antibodies to NETs measured by ELISA were significantly elevated in patients with primary APS and in SLE without aPL relative to the healthy controls [58]. In a recent larger cohort of primary APS, 45% of the aPL-positive patients had IgG and/or IgM anti-NET antibodies [59]. Importantly, an analysis of the associations of anti-NET antibodies with clinical manifestations revealed that IgG antibodies were associated with lesions affecting the white matter of the brain, while IgM antibodies were tracked with complement consumption.…”
Section: Anti-net Antibodiesmentioning
confidence: 89%
“…On the other hand, the presence of aPLs in vivo promotes coagulation and causes thrombosis. As a mechanism for causing thrombosis, antiphospholipid antibodies inhibit the activation of protein C, inhibit β2-glycoprotein-I (β2-GPI) that suppresses phospholipid-dependent coagulation reactions [94,95], inhibit or impair thrombomodulin [96] and heparan sulfate [97] on vascular endothelial cells, suppress prostacyclin production from vascular endothelial cells that inhibits platelet aggregation [98], and increase the production and release of VWF [99,100] and plasminogen activator inhibitor [101]. Clinical findings are often found in deep-vein thrombosis, thrombocytopenia, recurrent miscarriage/stillbirth (infertility), cerebral infarction, migraine, and livedo [102].…”
Section: Apsmentioning
confidence: 99%
“…In this issue of Arthritis & Rheumatology , a provocative serologic analysis by Zuo et al provides a novel perspective on autoantibody expression in patients with antiphospholipid antibodies (aPL) (1). As the data from a large patient cohort indicate, patients whose serum is persistently positive for APL, including those with the antiphospholipid syndrome (APS), produce IgM and IgG antibodies to neutrophil extracellular traps (NETs), a large DNA‐rich structure released by activated neutrophils (2,3).…”
Section: Figurementioning
confidence: 99%
“…As shown in their study, 45% of 389 patients with aPL, 309 of whom had APS, had anti‐NET antibodies. Of interest, the presence of the IgG anti‐NET antibodies was associated with white matter lesions, while IgM anti‐NET antibodies were associated with complement activation (1). In this and other studies in which anti‐NET antibodies have been quantified, the NETs in the supernatants of activated cells are partially digested with micrococcal nuclease to create an antigen preparation suitable for assay in microtiter plates.…”
Section: Figurementioning
confidence: 99%